Astra International: Innovation Asian style - WILLIAMSON, Peter J. (Institutional Knowledge at Singapore Management University, 2016)
It is 1 August 2015, and the 32nd InnovAstra Convention, an annual competition meant to showcase and recognise the innovation achievements of individuals, teams and business units in the Indonesian conglomerate PT Astra International Tbk (Astra), is just a fortnight away. Ekuslie Goestiandi is the head of the Corporate Centre that organised the InnovAstra Convention, and manages development programmes for facilitators to promote InnovAstra’s standards and values in the company. Astra’s employees have been inculcated with a spirit of striving towards continuous innovation from very early on in the company’s history. Over the past two decades, Astra has expanded the scope of innovation across all group companies to encompass all employees, including the top management. Despite initiatives such as the InnovAstra Convention, Astra’s leadership team is aware that much more is needed to be done for the group to successfully manage the challenges of the future. The business climate in Indonesia is expected to become far more volatile and demanding, influenced by intensified competition and rapid technological advances. In addition, the younger generation of employees and consumers will have different sets of needs and preferences that need to be understood and met. To manage these challenges, Astra has to plan for the ‘next level of innovation’ in the company, and that requires clear direction from the top. A key element of Astra’s future direction is establishing a “synergistic business chain” that enables different activities within each business and across businesses to become mutually supportive. The question Ekuslie is mulling over is: what would it take to bring Astra to the next level of innovative capability?